2020
DOI: 10.1111/dth.13240
|View full text |Cite
|
Sign up to set email alerts
|

Classification and mitigation of negative injection experiences with biologic medications

Abstract: Injection site reactions with biologic medications are encountered with variable frequency. Although there is no clear definition, they commonly manifest with pain and irritation at the injection site. Previously proposed reaction classification systems may be impractical or insufficient, and more intuitive nomenclature may benefit clinical dermatologists and patients. Negative injection experiences (NIE) are common reasons for biologic medication nonadherence. Here we provide clinical classifications and reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
(59 reference statements)
1
13
0
Order By: Relevance
“…Of note, any variations in ISP between originator and biosimilar biologics do not appear to reflect any differences in immunogenicity between these agents [23], with biosimilars reported to be effective and well tolerated in maintaining complete remission after the switch from the originator agent [24,25]. pH Bunke et al [26] suggested that the difference between the physiological pH of the tissue at Table 1 Factors contributing to subcutaneous injection-site pain Product-related factors Injection-related factors Patient-related factors • Formulation (ingredients, pH, buffers) [16,17,27,28,40] • Delivery volume [15,[32][33][34] • Needle gauge size [44] • Device type [49][50][51][52][53][54] • Injection speed [55][56][57][58] • Fluid viscosity [55] • Injection angle/technique [59,60] • Temperature of product [62,63] • Allergens [65,66] • Injection frequency [61] • Injection site [35] • Low body weight [68] • Injection anxiety/'needle phobia' [69,70] • Pain catastrophising [72] • Nocebo effect [73,74] • Female gender [67] • Fibromya...…”
Section: Product-related Factors Contributing To Sc Ispmentioning
confidence: 99%
See 4 more Smart Citations
“…Of note, any variations in ISP between originator and biosimilar biologics do not appear to reflect any differences in immunogenicity between these agents [23], with biosimilars reported to be effective and well tolerated in maintaining complete remission after the switch from the originator agent [24,25]. pH Bunke et al [26] suggested that the difference between the physiological pH of the tissue at Table 1 Factors contributing to subcutaneous injection-site pain Product-related factors Injection-related factors Patient-related factors • Formulation (ingredients, pH, buffers) [16,17,27,28,40] • Delivery volume [15,[32][33][34] • Needle gauge size [44] • Device type [49][50][51][52][53][54] • Injection speed [55][56][57][58] • Fluid viscosity [55] • Injection angle/technique [59,60] • Temperature of product [62,63] • Allergens [65,66] • Injection frequency [61] • Injection site [35] • Low body weight [68] • Injection anxiety/'needle phobia' [69,70] • Pain catastrophising [72] • Nocebo effect [73,74] • Female gender [67] • Fibromya...…”
Section: Product-related Factors Contributing To Sc Ispmentioning
confidence: 99%
“…Higher volumes of injection are typically associated with increased patient discomfort and sometimes pain at the site of administration, with less ISP reported where reduced volume is possible [15,[32][33][34]. The injection volume for a biologic generally ranges from 0.4-2.0 mL although it is typically restricted to B 1.5 mL to prevent injection pain, leakage and tissue distortion [15,35].…”
Section: Volumementioning
confidence: 99%
See 3 more Smart Citations